5S KAIZEN UNTUK MENINGKATKAN PRODUKTIVITAS KADER PKK KELURAHAN PONDOK BAMBU JAKARTA PADA BUDIDAYA TANAMAN PANGAN - Rimadias, Santi; Rasyid, Soelaeman; Hertingkir, Fajar (Jurnal Berdaya Mandiri, 2023)
In order to enhance the quality of families' nutrition, PKK cadres under the supervision of Pondok Bambu Village, East Jakarta are diversifying food crops by cultivating kale, spinach, caisim, tomatoes, and chilies. The community service program aims to educate PKK cadres in Pondok Bambu Village, East Jakarta about 5S Kaizen to boost their productivity in growing food crops. The service activities will take place over three days and will include lectures, discussions, and on-site assistance during the service process. The application of Kaizen in an environment can increase productivity by ensuring that all members of the organization are cognizant of the main goals, objectives, and measures of success. The 5S approach, which stands for Seiri (Sort), Seiton (Set in order), Seiso (Shine), Seiketsu (Standardize), and Shitsuke (Sustain), can be employed to implement Kaizen. Keywords: Kaizen, 5S, Mentoring, Productivity